MEASURING TEACHERS’ PEDAGOGICAL CONTENT KNOWLEDGE USING MANY-FACET RASCH MODEL - Maryati Maryati; Zuhdan Kun Prasetyo; Insih Wilujeng; Bambang Sumintono (LPMPP Universitas Negeri Yogyakarta, 2019)
In the context of teacher professional development and teacher certification, an objective measurement of teachers’ Pedagogical Content Knowledge (PCK) is requried. This research is a case study to measure teachers’ PCK within prospective middle school science teachers participating in an Indonesian teacher professional development program. The study used quantitative approach which involved multirater assessment analysed by Many-Facet Rasch Model (MFRM) to assess teachers’ PCK in teaching a specific topic, i.e. “The Particulate Nature of Matter” (PNM). Researchers developed a rubric for items to measure teachers’ enactment PCK for teaching that specific topic. The MFRM analysis of the data revealed item reliability, item validity, separation and unidimensionality fall within good category. The findings show prospective teachers need to improve their PCK specifically in terms of “knowledge of instructional strategies and representations for teaching science” dimension. However, for knowledge of science curriculum and knowledge of students’ understanding in science dimension, the findings show that the participants were competent.